2014
DOI: 10.1177/1088767914563389
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Honor Killings and the Perpetrators’ Experiences

Abstract: As a final part of a trilogy based on the same data set, this article adds to the growing body of knowledge on homicides against women by examining and identifying patterns, dynamics, and perpetrators' experiences in honor killings. In-depth interviews conducted with a sample of the perpetrators provide further insight into the factors behind the perpetrators' behavior, and the chain of events that may have been part of the context of the murder. Unlike two previous articles by this author, by exploring in as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
1
23
0
4
Order By: Relevance
“…Through court records and quotes made to the police, the data collected in this study showed many of the offenders provided justifications or rationalizations for their crimes beyond the overarching motivations identified. In a previous study, Doğan (2014c) conducted interviews with offenders of honor crimes to provide perspective into their behavior preceding the commission of the crime. Doğan (2014c) noted that within the offender's narrative, techniques of neutralization emerged, including denying the victim and appealing to higher loyalties (Sykes and Matza 1957).…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Through court records and quotes made to the police, the data collected in this study showed many of the offenders provided justifications or rationalizations for their crimes beyond the overarching motivations identified. In a previous study, Doğan (2014c) conducted interviews with offenders of honor crimes to provide perspective into their behavior preceding the commission of the crime. Doğan (2014c) noted that within the offender's narrative, techniques of neutralization emerged, including denying the victim and appealing to higher loyalties (Sykes and Matza 1957).…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…In a previous study, Doğan (2014c) conducted interviews with offenders of honor crimes to provide perspective into their behavior preceding the commission of the crime. Doğan (2014c) noted that within the offender's narrative, techniques of neutralization emerged, including denying the victim and appealing to higher loyalties (Sykes and Matza 1957). An avenue for future research is to analyze these open-source materials for themes based on neutralization theory to provide greater context to offender motivations.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…Hilangnya kehormatan disamakan dengan hilangnya nyawa. Membunuh adalah cara yang ditempuh untuk memulihkan kehormatan keluarga (Dogan, 2014: 3).…”
Section: Pendahuluanunclassified
“…Jealousy in romantic relationships is present in all societies and cultures and it involves a set of complex cognitive, emotional, physiological, and behavioral responses determined by a perceived threat to an intimate relationship by a rival, regardless of whether that threat is real or not (Elphinston, Feeney, Noller, Connor, & Fitzgerald, 2013;Gouveia, Silveira, Santos, Souza, & Belo, 2015;Pavela, Banai, & Šimic, 2014;Ramos, Yazawa, & Salazar, 1994). The diversity of such responses can be observed through the set of feelings associated with jealousy, such as anger, fear, sadness, excessive distrust, and may be accompanied by aggressive behavior (Buss, 2000;Doğan, 2016;Elphinston et al, 2013;Wigman, Graham-Kevan & Archer, 2008). Research shows that jealousy is a heterogeneous condition ranging from normal to pathological, with different degrees and levels of persistence manifested over time (Marazziti et al, 2010;Ramos, et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has clearly pointed out that excessive jealousy is a risk factor for violent behaviors in love relationships, with relationship breakups being one of the main factors leading to aggression (Buss, 2000;Dobash, R. E., Dobash, R. P., Cavanagh, Smith, & Medina-Ariza, 2007;Doğan, 2016;Dossi, Saliba, Garbin, C. A. S., & Garbin, A. J. I., 2008). In addition, women have indicated that jealousy associated with alcohol abuse is one of the main reasons for the occurrence of domestic violence (Crane, Hawes, Oberleitner, Mandel, & Easton, 2013).…”
Section: Introductionmentioning
confidence: 99%